Keynes, Bloomsbury and method. Issue 1 (2nd September 2017) - Dow, Geoff
Abstract: Maynard Keynes's precocious upbringing in Cambridge (including as a member of the Apostles) and, later, his involvement in the Bloomsbury group, allowed important methodological controversies to be acknowledged – initially through his father's sympathy towards anti-economistic ways of knowing. This burgeoned into an interdisciplinary distinctiveness, which easily sustained some later radicalisms in Keynesian and post-Keynesian political economy. The intellectual climate at the time additionally included European modernist movements in literature, the arts, philosophy, other social sciences and morals. We now know that many of the controversies characterising heterodox political economy had emerged in scholarly discussion generally; they became implanted (if contentiously) into social enquiry and political economy as they matured throughout the nineteenth century.